Risk, business cycles and financial crises: evidence from Islamic and conventional stocks - Tee, Lain-Tze; Kew, Si-Roei (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study examines whether business cycles and financial crises affect the risk of Islamic stocks compared to conventional stocks in Malaysia for the period 1997 to 2016. The findings conclude that business cycles play a crucial role in affecting stock risk. Specifically, stock risk tends to be higher during the economic contraction than during economic expansion for Islamic, conventional and all stocks. We further test whether Asian and Global financial crises exacerbate stock risk. The results document that the level of stock risk increases during financial crises. Moreover, we find that the impact of economic contraction and financial crises on increasing stock risk remain significant after controlling for various variables known to have effect on risks. In addition, we discover that the risk of Islamic stock is lower compared to those of conventional and all stocks during the economic contraction and financial crises. This recommends the diversification advantage and investment opportunity of the Islamic stocks during the periods of financial turbulence. The findings offer important insights to investors who are considering Islamic or conventional stocks as potential investment and to policymakers in evaluating stock risk in different economic states.